Novel beaded polymers from telechelic methacrylic ether esters - Pujari, N. S.; Trivedi, J.; Ingavle, Ganesh C.; Ponrathnam, S. (Reactive & Functional Polymers, 2006)
A series of telechelic dimethacrylic ether-esters (MEE) were prepared by solventless reaction of alpha,omega-dihydroxy poly(oxytetramethylene) (polytetrahydrofuran, PTHF) with phthalic anhydride and glycidyl methacrylate (GMA). MEE was polymerized with GMA as well as GMA-ethylene dimethacrylate (EGDM) to form porous beads. The terpolymer beads were observed using optical microscopy and SEM and characterized for internal pore volume, equilibrium volume-swelling ratio and dimethyl formamide and aqueous buffer regain. The morphology of the beads was dictated by the mole fraction and molecular weight of MEE in the feed. Porosity was found to increase with increase in molecular weight of MEE. Thus, porosity as high as 49%, 50% and 55% was observed with MEE of molecular weights 1580, 2580 and 3480, respectively. At a specific terpolymerization feed ratio of monomers, the terpolymers formed transform from gel like structure into a macroporous one, with increase in molecular weight of MEE. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: ether-ester dimethacrylates; macroporous; Pore size distribution; porosity; telechelics

Novel/conceptual floating pulsatile system using high internal phase emulsion based porous material intended for chronotherapy - Sher, Praveen; Ingavle, Ganesh C.; Ponrathnam, Surendra; Benson, James R.; Li, Nai-Hong; Pawar, Atmaram P. (AAPS Pharmscitech, 2009)
The aim of the present study was to design a novel/conceptual delivery system using ibuprofen, anticipated for chronotherapy in arthritis with porous material to overcome the formulation limits (multiple steps, polymers, excipients) and to optimize drug loading for a desired release profile suitable for in vitro investigations. The objective of this delivery system lies in the availability of maximum drug amount for absorption in the wee hours as recommended. Drug loading using 3(2) factorial design on porous carrier, synthesized by high internal phase emulsion technique using styrene and divinylbenzene, was done via solvent evaporation using methanol and dichloromethane. The system was evaluated in vitro for drug loading, encapsulation efficiency, and surface characterization by scanning electron, atomic force microscopy, and customized drug release study. This study examined critical parameters such as solvent volume, drug amount, and solvent polarity on investigations related to drug adsorption and release mostly favoring low-polarity solvent dichloromethane. Overall release in all batches ranged 0.98-52% in acidic medium and 71-94% in basic medium. These results exhibit uniqueness in achieving the least drug release of 0.98%, an ideal one, without using any release modifiers, making it distinct from other approaches/technologies for time and controlled release and for chronotherapy.
Keywords: chronotherapy; floating pulsatile drug delivery system; high internal phase emulsion; ibuprofen; multiparticulate porous carriers